Rwanda Economic Update, August 2017 : Sustaining Growth by Building on Emerging Export Opportunities - World Bank (World Bank, Kigali, 2017)
The 10th economic update comes at an important juncture for Rwanda. The country has entered the third decade of uninterrupted economic growth and social progress. Rwanda’s global income ranking improved from the seventh poorest in 2000 to the 20th in 2015, on the back of Rwanda’s strong commitment to good governance, the principles of market economy and openness. The growth, however, has been slowing down recently and is expected to remain subdued in 2017. Going forward, achieving Rwanda’s ambition of attaining middle-income status requires sustaining the average growth rate of the past two decades in the years to come. The vision 2050, and the new EDPRS, currently under preparation will provide the roadmap for adapting the economy to the evolving regional and global context and maintaining a growth rate that delivers poverty reduction and prosperity. In addition to presenting recent macroeconomic developments, this update also discusses the longer-term patterns of productivity and structural transformation and derives some broad lessons for growth strategy. The Rwanda Economic Update (REU) reports on and synthesizes recent economic developments, and places them in a medium term, regional, and global context. It analyses the implications of these developments and policies for the outlook of the economy. These reports attempt to make an analytical contribution to the implementation of Rwanda’s national development strategy. Each edition includes a special feature on a selected topic. The report is intended for a wide audience, including policy makers, business leaders, other market participants, the community of analysts engaged in Rwanda’s economy, and civil society.